Lecciones activas: estrategia para aumentar la actividad física de los escolares durante la jornada lectiva. [Physically active lessons: strategy to increase scholars´ physical activity during school time]. - Beatriz Polo-Recuero; Almudena Moreno-Barrio; Alfonso Ordóñez-Dios (Ramón Cantó Alcaraz, 2020)
The present study analyzes a strategy implemented in a public school in order to increase scholars´ physical activity levels during theoretical subjects. For this purpose, mini static bicycles under the desk, hereinafter bike desks, were integrated in the traditional classroom. Students pedal on these active desks while they pay attention to the lesson. After verifying its feasibility in 157 high school students, the influence of pedaling was tested on both students' mathematical and physical fitness competence. To this end, the intervention was focused on 27 same class students, randomly divided into a PEDAL intervention group (N = 14; 13.14 ± 0.36 years; 35.7% women), who used the bike desks during their four weekly math sessions, and in a control group (N = 13; 13.23 ± 0.44 years; 30.8% women) who attended their classes normally, with no significant previous differences between groups. From the post-test analysis, regarding physical fitness (20m shuttle run test) statistically significant differences were obtained in favor of the PEDAL group and, in terms of mathematical competence (statistical test, Community of Madrid 6th grade assessment) no significance was detected between both groups, although PEDAL group results were better. Therefore, schools should seek strategies, such as the one presented in this project, to provide physical activity opportunities.